Design of Surface Modified Acyclovir-loaded Graphene Oxide–Mesoporous Silica Nanocomposite: Optimization and In Vitro Characterization - Ketan B. Patil; Jayvadan K. Patel; Hardik H. Goswami; Arjun S. Chaudhari (Nano Biomedicine and Engineering)
Graphene oxide (GO) and mesoporous silica nanoparticle (MSN) have been documented as advanced nanocarriers for drug delivery due to their unique and versatile properties. The design of GO–MSN nanocomposite offers a large surface area, adjustable pore size, biocompatibility, and low cytotoxicity. The application of acyclovir (ACV) (BCS: III) is suffering from poor permeability, low bioavailability, etc. Hence, the use of GO–MSN nanocomposite for the delivery of ACV may overcome the limitations of ACV. Therefore, the present work aims to design the lipid-coated ACV-loaded GO–MSN (LC-ACV-GO–MSN) nanocomposites. In brief, the design of experiments (DoE, 32 response surface methodology) approach was preferred for the development of GO–MSN nanocomposite. The loading of ACV in nanocomposite was done passive loading whereas the coating of lipids was done using a modified thin film hydration technique. At last, different spectral characterizations were performed. The output demonstrated that the entrapment efficiency of ACV-MSN and ACV-GO–MSN was 51.13% and 71.86%, respectively. Afterward, the designed LC-ACV-GO–MSN and ACV-GO–MSN nanocomposite shows 93.40% and 80.74% in vitro drug release, respectively. In conclusion, the design of LC-ACV-GO–MSN nanocomposite using optimized GO–MSN followed lipid coating offers the modified release. Therefore, in the future, LC-ACV-GO–MSN nanocomposite can be used for the delivery of ACV and other drug molecules with a high payload and enhanced release profile. We hope the current proof of concept may provide advantages over existing methods and emphasize the significance of protocells in cargo delivery systems.